If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(6n + 5) = -114 Reorder the terms: 6(5 + 6n) = -114 (5 * 6 + 6n * 6) = -114 (30 + 36n) = -114 Solving 30 + 36n = -114 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 36n = -114 + -30 Combine like terms: 30 + -30 = 0 0 + 36n = -114 + -30 36n = -114 + -30 Combine like terms: -114 + -30 = -144 36n = -144 Divide each side by '36'. n = -4 Simplifying n = -4
| 18-6t=30 | | 5x^2-16x=-2x^2-5x-4 | | 2(x^2-4x)=24 | | 5+3x+-7x=53 | | 2+18=5x+3 | | 62=-4(1-2x)+3x | | 7x^2y+6y=2x | | 9-4n=12-n | | 6(0)+5y=9 | | (2x+9)(x-3)=0 | | 4x+8=124 | | 64=4(4-2r) | | 37x+19=6(6x+8) | | x+5/3=2-x+5/2 | | 5x+3=x+8 | | 7a-7=2a-22 | | x*3.14*2=7.34 | | -80=-4(-6x+2) | | y=-17x+16 | | 5x+5x-9=-9 | | 3a+(b+3)i=9+8i | | -6(n-5)=114 | | 4x-8=2(x+2) | | 78=-4+2(6n+5) | | -5(1+3x)-2=68 | | logx-log(2x-3)=2 | | 19w+18=6 | | x^2-4x=24 | | 3-8z=0 | | 6x+7y=28 | | 9(x-1)-7=3x+6(-3+x) | | 4x^3+23x^2+15x=0 |